Experimental study on the treatment of norepinephrine transporter-overexpressing pheochromocytomas and paragangliomas: a synthetic lethality strategy combining 131I-MIBG with PARP inhibitors - Song, Jieping; Zhang, Lulu; Qiu, Fan; Shi, Xiumin; Tian, Rui; Zhang, Chuan; Li, Xiaoyuan; Wang, Feng (Frontiers in Oncology, 2025)
IntroductionPheochromocytomas and paragangliomas (PPGLs) are associated with poor prognosis especially in patients with metastatic spread. This study aims to investigate the therapeutic potential of 131I-MIBG and the PARP inhibitor fluzoparib monotherapies and their combination on two distinct PC12-derived stable cell lines: PC12-NET cells and PC12-NET-SDHB cells.MethodsLentiviral transduction was used to generate PC12-NET cells overexpressing the norepinephrine transporter (NET) and PC12-NET-SDHB cells with suppressed succinate dehydrogenase subunit B (SDHB) expression. The specificity of PC12-NET cells to the 131I-MIBG was confirmed through desipramine inhibition assays. Subsequently, the synergistic effects of 131I-MIBG and fluzoparib monotherapies and their combination were assessed in vitro through proliferation assays, cell cycle analysis and apoptosis analysis in both cell lines.ResultsNET overexpression significantly enhanced 131I-MIBG uptake in PC12-NET cells, confirming NET expression as a critical determining of 131I-MIBG therapeutic efficacy. The combination of 131I-MIBG with fluzoparib exhibited substantial synergistic effects in PC12-NET cells, leading to a significant G2/M phase arrest and a marked increase in apoptosis compared to monotherapy, particularly where monotherapy alone was ineffective. Notably, although low expression of the SDHB did not alter cell proliferation in response to 131I-MIBG treatment, PC12-NET-SDHB cells exhibited a greater sensitivity to fluzoparib-induced G2/M phase arrest than PC12-NET cells.DiscussionThe combined of 131I-MIBG with PARP inhibitor demonstrated a synergistic antitumor effect in PC12-NET cells. While PC12-NET-SDHB cells display comparable sensitivity to 131I-MIBG as PC12-NET cells, they exhibited heightened responsiveness to PARP inhibitor treatment.